2021
DOI: 10.1002/acr.24384
|View full text |Cite
|
Sign up to set email alerts
|

Functional Ability and Health‐Related Quality of Life in Randomized Controlled Trials of Tocilizumab in Patients With Juvenile Idiopathic Arthritis

Abstract: Objective To evaluate changes in health‐related quality of life (HRQoL) and disability in children with systemic juvenile idiopathic arthritis (JIA) or polyarticular JIA treated with tocilizumab. Methods Secondary analyses of two double‐blind, placebo‐controlled trials of intravenous tocilizumab in children with active systemic JIA or polyarticular JIA were conducted. Patient‐reported outcomes of disability (Childhood Health Assessment Questionnaire [C‐HAQ]), HRQoL (Child Health Questionnaire Parent Form 50 [C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Two studies in patients with JIA (ages 2 to 17 years) who were treated with either tocilizumab or golimumab have demonstrated improvements in PROs (CHAQ‐DI, Child Health Questionnaire [CHQ]) over 16 weeks of treatment (37,38). Other studies in patients ages between 8 and 24 years have also reported improvements in PROs (CHAQ‐DI, CHQ, Health Utilities Index mark 3) with both short‐ and long‐term bDMARD treatment (39–41). Two registries have reported improvements in health‐related quality of life (HRQoL) in patients with JIA treated with either adalimumab plus MTX versus MTX over 1 year or with IV or SC abatacept over 5 years (42,43).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Two studies in patients with JIA (ages 2 to 17 years) who were treated with either tocilizumab or golimumab have demonstrated improvements in PROs (CHAQ‐DI, Child Health Questionnaire [CHQ]) over 16 weeks of treatment (37,38). Other studies in patients ages between 8 and 24 years have also reported improvements in PROs (CHAQ‐DI, CHQ, Health Utilities Index mark 3) with both short‐ and long‐term bDMARD treatment (39–41). Two registries have reported improvements in health‐related quality of life (HRQoL) in patients with JIA treated with either adalimumab plus MTX versus MTX over 1 year or with IV or SC abatacept over 5 years (42,43).…”
Section: Discussionmentioning
confidence: 93%
“…‡ For the 2-to 5-year-old cohort, the median (IQR) values at baseline were absolute numbers of missed school days, 1.0 (0.0-5.0); number of paid care days, 0.0 (0.0-0.0); and number of missed parent/caregiver activity days, 3.0 (0.0-7.0). (39)(40)(41). Two registries have reported improvements in healthrelated quality of life (HRQoL) in patients with JIA treated with either adalimumab plus MTX versus MTX over 1 year or with IV or SC abatacept over 5 years (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…During the biologic era, disability in patients with JIA has decreased. A study found that patients with systemic JIA and patients with polyarticular JIA who were treated with tocilizumab had significantly reduced disability [ 29 ]. Tanya, et al reported disability and joint damage to be rare in their Singaporean JIA cohort; and 36% of their patients were treated with biologic agents [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A CHQ pain score of 100 indicates no pain. The CHQ pain score had been applied in pain research earlier (46,67). We categorized CHQ pain score 0-30 as severe, 40-60 as moderate, and 70-90 as mild pain.…”
Section: Discussionmentioning
confidence: 99%
“…We believed that the grading of pain severity should be independent from daily activities because the reference frames for daily activities would differ greatly (Papers I-III). Questions on pain from CHQ were used in previous research in children with CP (46,50,81), and recently in treatment evaluation in the children with juvenile idiopathic arthritis (67).…”
Section: Choice Of Variablesmentioning
confidence: 99%